Nucleosynthesis for SN 1987A from single-star and binary-merger progenitors. (2nd July 2019) - Fröhlich, C; Curtis, S; Ebinger, K; Ghosh, S; Menon, A; Heger, A; Perego, A; Thielemann, F-K
Abstract: We apply the parametrized, spherically symmetric explosion method PUSH to two sets of pre-explosion models suitable for SN 1987A: blue supergiants (BSGs) resulting from the merger of a main sequence star with a giant and red supergiants (RSGs) representing the end point of single-star stellar evolution. For each model, we perform a calibration of the PUSH method to the observational properties of SN 1987A and calculate the detailed explosive nucleosynthesis yields. We find that such a calibration to SN 1987A is only possible for one of the BSG models. We compare the yields from this model with the yields from the best-fit RSG model. The largest differences are found for nuclei in the mass range of 20 ≤ A ≤ 40 which are mostly synthesized pre-explosion. We predict a neutron star with a gravitational mass of 1.48 M ⊙ from the BSG model and a neutron star of 1.41 M ⊙ from the RSG model.